Hyperhomocyst(e)inemia in chronic stable renal transplant patients - Machado, David José de Barros; Paula, Flávio Jota de; Sabbaga, Emil; Ianhez, Luiz Estevan (Revista do Hospital das Clínicas, 2000)
PURPOSE: Hyperhomocyst(e)inaemia is an important risk factor for atherosclerosis, which is currently a major cause of death in renal transplant patients. The aim of this study was to assess the influence of immunosuppressive therapy on homocyst(e)inemia in renal transplant recipients. METHODS: Total serum homocysteine (by high performance liquid chromatography), creatinine, lipid profile, folic acid (by radioimmunoassay-RIA) and vitamin B12 (by RIA) concentrations were measured in 3 groups. Group I patients (n=20) were under treatment with cyclosporine, azathioprine, and prednisone; group II (n=9) were under treatment with azathioprine and prednisone; and group III (n=7) were composed of renal graft donors for groups I and II. Creatinine, estimated creatinine clearance, cyclosporine trough level, lipid profile, folic acid, and vitamin B12 concentrations and clinical characteristics of patients were assessed with the aim of ascertaining determinants of hyperhomocyst(e)inemia. RESULTS: Patient ages were 48.8 ± 15.1 yr (group I), 43.3 ± 11.3 yr (group II); and 46.5 ± 14.8 yr (group III). Mean serum homocyst(e)ine (tHcy) concentrations were 18.07 ± 8.29 mmol/l in renal transplant recipients; 16.55 ± 5.6 mmol/l and 21.44 ± 12.1 mmol/l respectively for group I (with cyclosporine) and group II (without cyclosporine) (NS). In renal donors, tHcy was significantly lower (9.07 ± 3.06 mmol/l; group I + group II vs. group III, p